Gondolatok a Középső-Józsefváros rehabilitációjának társadalmi összefüggéseirő - Ladányi, János (Tér és Társadalom, 1992)
The present study was written on the basis of the papers that were prepared by the author on the rehabilitation of Central-Josephstadt as contributions to a detailed urban plan. In the first part of the study, the author gives a historical overview of the urban regulations influencing the development of this part of the city. As a summary of his historical argumentations, the author states that the beginning of the "slummification process" cannot be considered to be the direct consequence of the ecological position of this part of the city. In order to support the above statement he declares that speeded-up "slummification" was not caused by spontaneous tendencies, but rather by the nationalization of the majority of flats in this district as a first step, and then by neglecting the necessary reconstruction works for more than 50 years. Though the above tendencies were typical of other parts of the capital city, they took place as widespread processes fundamentally influencing the socio-spatial structure of the city only in the districts of Inner Pest, primarily because the decisive majority of the nationalized flats can be found in this part of Budapest. After the historical overview, the author presents and analyzes his data on that part of the population in this area who are poor, gypsy, unemployed and migrated from the countryside only recently. These data are compared with those of the Central-Josephstadt as a whole, with some parts of this area, and with the averages of the whole capital city. In the last part, the study deals with the possible alternatives handling the "slummification process" by means of urban planning and urban management, with the chances of their realization, and with their expected social consequences.